The Effect of Progressive Muscle Relaxation Therapy on Lowering Blood Pressure in Adult Clients with Hypertension - Kamalita Rosyada; Aisyiah Aisyiah; Tommy Jemmy Fransiscus Wowor (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Hypertension ranks the fifth most common cause of death in Indonesia. Progressive muscle relaxation therapy can produce a calm heart rate that can lower blood pressure and reduce stress hormone levels so that it can help lower high blood pressure. This study aims to determine whether there is an effect of progressive muscle relaxation exercises on reducing blood pressure. Quasy Experimental Design using one group pre-post test method design. The population of this study were 30 hypertensive patients who were registered at the study site. The sample uses the total sampling method. All samples were given progressive muscle relaxation therapy intervention which was carried out by tightening and relaxing muscles in one part of the body at a certain time to provide physical relaxation which was carried out in 4 sessions consisting of 14 movements for 25-30 minutes carried out twice a day for 2 days. Mean systolic blood pressure before intervention was 138.67 mm/Hg and diastolic before 84.33 mm/Hg. The mean systolic blood pressure after intervention) was 125.67 mm/Hg and diastolic pressure was 77.33 mm/Hg. There is the effect of progressive muscle relaxation therapy on the reduction of both systolic and diastolic blood pressure with a P value (0.000) <α (0.05). Progressive muscle relaxation therapy has an effect on lowering blood pressure in adult clients with hypertension.